Respiratory function is associated to marathon race time - Salinero, J. J.; Soriano, M. L.; Ruiz-Vicente, D.; Gonzalez-Millan, C.; Areces, F.; Gallo-Salazar, C.; Abian-Vicen, J.; Lara, B.; Del Coso, J. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The purpose of this study was to analyze the relationship between marathon race time and expiratory pulmonary parameters in a heterogeneous group of amateur marathoners.